O najdawniejszej włoskiej leksykografii dwujęzycznej, znanej i nieznanej - Krauze, Julia (Załącznik Kulturoznawczy, 2023)
On the Earliest Italian Bilingual Lexicography, Known and Unknown Since the Latin language became part of the education system, all kinds of grammatical compendiums, dictionaries, and commentaries on classical works of Greco-Roman literature have been an indispensable tool for exploring its intricacies. The turn of the 14th and 15th centuries was extremely interesting in this respect as it abounded in diverse and original works of this type, especially in Italy. The issues of studiorum humanitatis are discussed in such works as Elegantiae Linguae Latinae by Lorenzo Valle, Regulae grammaticales by Guarino Guarini, Epitoma seu Regulae constructionis and Latini sermonis emporium by Antonio Mancinelli, or the less known bilingual Glossarium by Jacopo Ursello from Roccantica. The books testify to teachers’ intentions to respond to the specific educational needs existing at that time, when it was necessary to educate students in written, spoken, and—to an increasing extent—Vulgar Latin. This article analyzes the above-mentioned Latin textbooks by Antonio Mancinelli and Jacopo Ursello, in which various aspects of Italianization operate in the light of the most important lexicographic sources of the era.